2010
DOI: 10.1155/2010/470785
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Rapid RP‐HPLC Method for the Estimation of Esmolol Hydrochloride in Bulk and Pharmaceutical Dosage Forms

Abstract: A reverse phase HPLC method is described for the determination of esmolol hydrochloride in bulk and injections. Chromatography was carried on a C18column using a mixture of acetonitrile, 0.05 M sodium acetate buffer and glacial acetic acid (35:65:3 v/v/v) as the mobile phase at a flow rate of 1 mL/min with detection at 275 nm. The retention time of the drug was 4.76 min. The detector response was linear in the concentration of 1-50 μg/mL. The limit of detection and limit of quantification was 0.614 and 1.86 μg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…The results in Table 3 showed that the methods are successful for the determination of drugs and that the excipients in the dosage forms do not interfere. The results are compared to the available validated reported [14][15][16][17][18] methods on each drug and the results agree well with the claim and also are in agreement with the results obtained by the literature method. Statistical analysis of the results using Student's t-test for accuracy and F-test for precision revealed no significant difference between the proposed methods and the literature method with respect to accuracy and precision.…”
Section: Application To Formulationssupporting
confidence: 84%
“…The results in Table 3 showed that the methods are successful for the determination of drugs and that the excipients in the dosage forms do not interfere. The results are compared to the available validated reported [14][15][16][17][18] methods on each drug and the results agree well with the claim and also are in agreement with the results obtained by the literature method. Statistical analysis of the results using Student's t-test for accuracy and F-test for precision revealed no significant difference between the proposed methods and the literature method with respect to accuracy and precision.…”
Section: Application To Formulationssupporting
confidence: 84%
“…The methods which were reported in the literature for the determination of ESM includes Spectrophotometry [45][46][47][48][49][50] , HPLC 51 and chromatography 52,53 methods. Since the abovementioned methods are complex and expensive, there is a need to develop simple, less expensive, and more selective method for the determination of ESM.…”
Section: Esmolol: (Esm) (mentioning
confidence: 99%
“…Most HPLC methods reported are useful in estimating Esmolol hydrochloride in human plasma [9][10][11][12][13] and biological fluids [14]. HPLC [15,16] methods have been reported for determination of ESM in pharmaceutical injections.…”
Section: Esmolol Hydrochloridementioning
confidence: 99%